Pengaruh Pemanfaatan Dana Desa Terhadap Pembangunan Infrastruktur di Desa Lubuk Terap Kecamatan Bandar Petalangan Kabupaten Pelalawan - Nurul Atifah; Wahyu Hamidi; Selly Prima Desweni (Journal of Social and Policy Issues, 2023)
The purpose of this research is to examine how the residents of Lubuk Terap, located in the Bandar Petalangan District of Pelalawan Regency, have used village funds to improve the village's infrastructure. Primary information was used for this study. Both quantitative and qualitative approaches were used to analyze the data in this study. Lubuk Terap is located in the Bandar Petalangan District of the Pelalawan Regency in Indonesia, and the analysis reveals that the village's simultaneous use of village funds has a significant impact on infrastructure development in the village. The R2 value, which represents the proportion of variance explained by the model, is 0.265, or 26.5%. This means that adjustments to how the village spends its money account for 26.5% of the observed changes in the development infrastructure of Lubuk Terap. Lubuk Terap village's development infrastructure has changed due to a combination of factors, only 26.5% of which are accounted for by the variables used in this analysis.